1987
DOI: 10.1161/01.hyp.10.5_pt_2.i4
|View full text |Cite
|
Sign up to set email alerts
|

The Li+-Na+ exchange and Na+-K+-Cl- cotransport systems in essential hypertension.

Abstract: SUMMARY This review examines the physiological functions of the Li + -Na + exchanger and Na + -K+-CI" cotransport system in human red blood cells. Both transporters are family aggregated and determined mainly by genetic factors; they are present in kidney and vascular cells, where they are regulated by vasoactive substances. To assess the physiological function of these two transporters, we investigated their kinetic and equilibrium properties, and their modulation by vasoactive substances. Recent studies in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
1
6
0
1
Order By: Relevance
“…Volume and pH regulatory actions of the Na+-H exchange system in smooth muscle cells could influence vascular reactivity and therefore peripheral vascular resistance. 23 The Gubbio data confirm the previously reported independent association between plasma uric acid and countertransport in men24 and expand this finding to women. This association could be an indication of a direct relation between Na-Li CT in red blood cells and renal proximal tubular absorption of uric acid.…”
Section: Discussionsupporting
confidence: 86%
“…Volume and pH regulatory actions of the Na+-H exchange system in smooth muscle cells could influence vascular reactivity and therefore peripheral vascular resistance. 23 The Gubbio data confirm the previously reported independent association between plasma uric acid and countertransport in men24 and expand this finding to women. This association could be an indication of a direct relation between Na-Li CT in red blood cells and renal proximal tubular absorption of uric acid.…”
Section: Discussionsupporting
confidence: 86%
“…We can offer no explanation for the cause of this correlation, as the mechanisms relating high RBC Li + -Na + countertransport and hypertension are still uncertain, but the finding of a significant inverse relation in the subgroup with higher MAP provides further support for the contention that Li + -Na + countertransport or an analog system is intimately linked to the pathophysiological basis of hypertension in some individuals. In this regard, the recent observations reported by Canessa et al 27 that RBC Li + -Na + countertransport may be a mode of Na + -H + exchange and by Livne et al 28 that platelet Na + -H + exchange is increased in essential hypertension suggest that abnormalities of the ubiquitous transmembrane Na + -H + exchange may be a fruitful area for future research into the cellular mechanism causing human hypertension.…”
Section: Resultsmentioning
confidence: 95%
“…Yap 34 it seems that the regulatory defect causing an increased \ mtI for Li + r Na + 0 countertransport in essential hypertension is intracellular, and it has been suggested that measurements of Li + influx and efflux may not be congruent. 37 In addition, our patients were younger, had milder hypertension and presumably had less severe left ventricular hypertrophy, since we used echocardiographic measurements while Yap et al 35 applied electrocardiographic criteria. Thus, the two studies may not be strictly comparable, and although it appears that in our study, in patients at the earliest stage of hypertension, an elevated V^ for RBC Li + -Na + countertransport is not associated with left ventricular hypertrophy, it remains possible that as blood pressure rises, the course of progression of hypertrophy may be different.…”
Section: Discussionmentioning
confidence: 99%